A Review of the Ethics and Legal Principles of the Use of Artificial Intelligence in Student Learning in the Digital Era - Jaka Tiwana Alfianda; Mustika Mega Wijaya (Journal of Law, Society and Living Norms, 2025)
This article discusses the ethical and legal implications of the use of Artificial Intelligence (AI) by students in the learning process in the digital era. The rapid development of AI technology, such as ChatGPT, Grammarly, and similar platforms, has changed the educational paradigm by providing ease of access to information and completion of assignments. However, this phenomenon also poses serious challenges, including potential violations of academic integrity, misuse of technology, risks to personal data protection, and the digital access gap. This study uses a normative juridical method with a conceptual and legislative approach to analyze the legal and ethical basis for the use of AI in educational settings. The results of the study indicate that the lack of regulations specifically governing the use of AI by students can create a normative vacuum and legal vulnerabilities. Therefore, the integration of digital ethics literacy into the curriculum, the development of data protection policies in educational institutions, and multi-stakeholder collaboration are needed to ensure that the use of AI aligns with the principles of legality, justice, child protection, benefit, and accountability in the national education system.